The Survival Benefit and Safety of Splenectomy for Gastric Cancer With Total Gastrectomy: Updated Results† - Yang, Kun; Zang, Zhi-Yun; Niu, Kai-Fan; Sun, Li-Fei; Zhang, Wei-Han; Zhang, Yue-Xin; Chen, Xiao-Long; Zhou, Zong-Guang; Hu, Jian-Kun (Frontiers in Oncology, 2021)
Background: Splenectomy was traditionally performed to dissect the splenic hilar lymph nodes. Considering the important functions of spleen, whether splenectomy would bring beneficial to gastric cancer patients is debatable. This meta-analysis aimed to make an updated evaluation on the effectiveness and safety of splenectomy. Methods: Literature searches were performed to identify eligible RCTs concerning effectiveness or safety of splenectomy with gastrectomy from PubMed, MEDLINE, CBMdisc, EMBASE and Cochrane Central Register of Controlled Trials. Two reviewers completed the study selection, data extraction and quality assessment independently. The meta-analyses were performed by RevMan 5.3. Results: A total of 971 patients from four studies were included (485 in splenectomy group and 486 in spleen preservation group). Splenectomy did not increase 5-year overall survival rate (RR=1.05, 95% CI: 0.96, 1.16), nor increase postoperative mortality (RR=1.21, 95% CI: 0.41, 3.54). However, the analysis demonstrated that gastrectomy with splenectomy had significantly higher incidence of postoperative complications (RR=1.80, 95% CI: 1.33, 2.45). No significant differences were found in terms of the number of resected lymph nodes and reoperation rate, however, splenectomy had a tendency to prolong the duration of surgery and hospital stays. Subgroup analyses indicated that splenectomy could not increase overall survival rate for either whole or proximal gastric cancer. Sensitivity analyses also found similar results compare to the primary analyses. Conclusions: Splenectomy cannot benefit the survival of patients with tumor located at lesser curvature, it could increase postoperative morbidity instead.